GLOBAL ANALYSIS OF THE RELATIONSHIP BETWEEN PRECIPITATION AND VEGETATION DYNAMICS DERIVED FROM NOAA/AVHRR-NDVI (ANALISIS GLOBAL DINAMIKA CURAH HUJAN DAN VEGETASI BERDASARKAN INDEKS VEGETASI NOAA/AVHRR) - Eleonora Runtunuwu; Haris Syahbuddin (Agromet, 2005)
The study of changes in global precipitation patterns is a key element in the ongoing research of climate change. There are also changes that occur over the land surface, such as in vegetation, which are associated with changes in precipitation. However, a better understanding of precipitation- vegetation relationships on various time and space scales is needed.There were many studies on relationship between rainfall to NDVI such as in East Africa1), Bostwana2), Sahel3), Amazon and Northeastern Brazil4), China5), and also in global scale6)7). From those studies, the relation of precipitation and NDVI is complex, such as reported by Kerr8) that its relationship was linear in Senegal, while by Lu5) the relationship was quadratic in China. Additionally, Milich and Weiss3) found that the relationship was inconsistent from the year to the year in Sahel, Africa.Hence, this paper attempts to explore the relationship between climate variables and the vegetation dynamic derived from NOOA/AVHRR-NDVI value, based on either spatial scale or point data. The authors also tried to investigate the possibility to study the global environmental change by using satellite data.